Pengaruh Pengembangan Karir Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT. Media Bhadrika Raya (MBR) di Tangerang - Milenia Agustina Saraswati; Sam Cay (Jurnal Bintang Manajemen, 2024)
The purpose of this research is to determine the influence of career development and work discipline on employee performance at PT. Media Bhadrika Raya (MBR) in Tangerang. The method used in this research is quantitative. The sampling technique used the Slovin formula and a sample of 70 respondents was obtained. Data analysis uses validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, hypothesis testing and coefficient of determination. The results of this research show that career development and work discipline simultaneously have a significant effect on employee performance with the regression equation Y = 10.039 + 0.445 X1 + 0.298 X2. Partial hypothesis testing shows that partial career development has a positive and significant effect on employee performance with a calculated t value > t table or 5.767 > 1.996, thus H0 is rejected and H1. Work discipline partially has a positive and significant effect on employee performance with a calculated t value > t table or 2.642 > 1.996, thus H0 is rejected and H2 is accepted. Simultaneously testing the hypothesis showed that the calculated F value > F table or 32.257 > 3.13 means that career development and work discipline have a positive and significant effect on employee performance, thus H0 is rejected and H3 is accepted. The coefficient of determination value is 49.1%, this gives the conclusion that career development and work discipline have an influence of 49.1% on employee performance, while the rest is influenced by variables not discussed in this research.